Creation and implementation of a library interactive media for the documentation of the shoe making process in Marikina - Legaspi, Charlotte Coleen D. (School of Library and Information Studies, University of the Philippines, Diliman, 2018)
Shoemaking is an intangible cultural heritage of Marikina City. With the goal of documenting the shoemaking craft and arts of Marikina City through photos and interviews, the project conceptualized and created an interactive media that provided a fun and easy way to learn about shoemaking process. The interactive media was launched at the Marikina City Library and was also presented and distributed to be Marikina Shoe Industry Development Office. The researcher consulted the Marikina Shoe Industry Development Office (MASIDO), a department in the city government responsible for the footwear and leather goods industry of Marikina City, for the shoemaking process. The researcher also scheduled interviews with the oldest shoe manufacturer and shoemakers in the city.